International Student Engagement in Higher Education : Transforming Practices, Pedagogies and Participation - Kettle, Margaret (Blue Ridge Summit, PA : Multilingual Matters, 2017)
Hand-in-hand with the continuing drive to recruit international students to Western universities goes an interest in student engagement. However, it is often unclear exactly what is meant by engagement. This book goes beyond the policy rhetoric to provide a practice-based explication of international student engagement and its enabling institutional conditions. By utilising a social practice conceptual model, the book explains the multiple dimensions of engagement that are often conflated in policy: the antecedents to engagement, the actions of engaging, and the achievements and outcomes of engagement. As a result, the book is able to address issues such as how English comes to matter in international student academic practice; the teaching and assessment approaches that promote international student engagement; and the metacognitive, cognitive and affective strategies that international students use to achieve academic and personal transformation.
Frontmatter -- Contents -- Preface -- 1. The Globalisation and Internationalisation of Higher Education -- 2. International Students in the Western Academy: Representations Across Time -- 3. Conceptualising International Student Engagement -- 4. University People and Places: Diversity in Action -- 5. English: What Counts in the Academy -- 6. Teaching: Generating Learning and Participation -- 7. Crafting Lives: Action, Austerity, Aesthetics -- 8. International Student Engagement in Higher Education -- References -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Nov 2018)
Keywords: English for Academic Purposes; English in the academy; international higher education; international student engagement; international student participation; International students; Student Engagement; teaching and assessment for diversity